Jadwiga Kiwerska, Bogdan Koszel, Maria Tomczak, Stanisław Żerko, Polityka zagraniczna zjednoczonych Niemiec [The Foreign Policy of the United Germany], Instytut Zachodni, Poznań 2011, pp. 400 - Seklecka, Natalia (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14761